The Treatment of Acute Diaphyseal Long-bones Fractures with Orthobiologics and Pharmacological Interventions for Bone Healing Enhancement: A Systematic Review of Clinical Evidence - Marongiu, Giuseppe (Bioengineering (Basel), 2020)
Background: The healing of long bones diaphyseal fractures can be often impaired and eventually end into delayed union and non-union. A number of therapeutic strategies have been proposed in combination with surgical treatment in order to enhance the healing process, such as scaffolds, growth factors, cell therapies and systemic pharmacological treatments. Our aim was to investigate the current evidence of bone healing enhancement of acute long bone diaphyseal fractures. Methods: A systematic review was conducted by using Pubmed/MEDLINE; Embase and Ovid databases. The combination of the search terms “long-bones; diaphyseal fracture; bone healing; growth factors; cell therapies; scaffolds; graft; bone substitutes; orthobiologics; teriparatide”. Results: The initial search resulted in 4156 articles of which 37 papers fulfilled the inclusion criteria and were the subject of this review. The studies included 1350 patients (837 males and 513 females) with a mean age of 65.3 years old. Conclusions: General lack of high-quality studies exists on the use of adjuvant strategies for bone healing enhancement in acute shaft fractures. Strong evidence supports the use of bone grafts, while only moderate evidence demineralized bone matrix and synthetic ceramics. Conflicting results partially supported the use of growth factors and cell therapies in acute fractures. Teriparatide showed promising results, particularly for atypical femoral fractures and periprosthetic femoral fractures.